Relationship between product involvement and brand loyalty. - Chan, Mei Ling. (2008)
Recognizing brand loyalty as a determinant to sustainability and thus the success of a company in today’s competitive business environment. We see the need to understand one of the core underlying factors, Product Involvement, in explaining Brand Loyalty.